Anti-influenza mechanism of phenolic phytochemicals from Canarium album (Lour.) DC. leaf extract. (28th June 2022) - Xiao, Mengjie; Lim-Ho Kong, Bobby; Zhang, Yahui; Yang, Yinhua; Lu, Jiaqi; Lee, Hung-Kay; Cao, Fei; Shaw, Pang-Chui
Abstract: Ethnopharmacological relevance: Canarium album (Lour.) DC. belongs to the Burseraceae family. Its leaf, named as Ganlanye (GLY), was recorded to treat warm disease symptoms via clearing lung heat and toxicants in medical classics. Its aqueous extract had anti-influenza activity in our previous phenotypic screening. However, its active components and mechanism were not identified. Aim: We aim to isolate the anti-influenza phytochemicals from GLY extract and explore its anti-flu mechanism. Material and methods: Influenza A virus infected MDCK cells were used to test the compounds and fractions. Structural analyses of new compounds were performed via NMR calculation with the combination of DP4plus probability method and computed electronic circular dichroism (ECD). Hemagglutination inhibitory assay and neuraminidase inhibitory assay were performed to find the target protein. Molecular docking and recombinant virus were used to confirm the action site of the three new canaroleosides. Results: Three new phenolic glycosides, canaroleosides A−C (1 –3 ), and three known flavonoids (4 –6 ), were isolated from the GLY aqueous extract and their anti-influenza virus mechanism was revealed. The absolute configurations of 1 −3 were determined by ECD method, with the structure of the 2, 5-dihydroxybenzoic acid moiety in 1 assigned by NMR calculation. Compound 1 was found to suppress both hemagglutinin and neuraminidase activities. Compounds 2, 3 4 and 6 inhibited neuraminidase, while compound 5 inhibited hemagglutinin. 1 –3 could interact with Arg152 of the viral neuraminidase based on the result of molecular docking and reverse genetics. Conclusion: Six phytochemicals were isolated from GLY aqueous extract and found to inhibit influenza A strains. They were found to interact with hemagglutinin or neuraminidase and canaroleosides 1 –3 could interact with Arg152 of the viral neuraminidase. This study provided more evidence on the anti-influenza effect of Ganlan and laid the foundation for further generation of potent NA inhibitors. Graphical abstract: Image 1